(untitled) (Scientific journal of the Fergana State University, 2024)
Family and family values occupy an important place in the consciousness and life of Uzbek citizens, which is reflected in the legal sphere and social policy of the state. The problems of the family, raising the younger generation in accordance with high spiritual and socio-ethnic criteria in Uzbekistan have deep historical, philosophical and historical-pedagogical roots. This article explores sociocultural and ethnic characteristics in the upbringing of youth in Uzbek families, as well as the influence of the experience of older family members on the development of younger generations.